Voting Right Rotation, Behavior of Committee Members and Financial Market Reactions : Evidence from the U.S. Federal Open Market Committee - Ehrmann, Michael (IMF Working Papers; Working Paper ;, 2022)
Which Federal Reserve Bank presidents vote on the U.S. monetary policy committee depends on a mechanical, yearly rotation scheme. Rotation is without exclusion: nonvoting presidents do attend and participate in the meetings of the committee. We test two hypotheses about the dependence of presidents' behavior on voting status. (i) Loss compensation: presidents compensate the loss of the right to vote with an increased use of speeches and contributions. (ii) Motivation: presidents complement the right to vote with an increased use of speeches and contributions. The evidence favors the motivation hypothesis. Also, in years that presidents vote, their speeches move financial markets less than in years they do not vote. We argue that this vote discount is consistent with presidents' communication behavior.